2017
DOI: 10.1002/nvsm.1596
|View full text |Cite
|
Sign up to set email alerts
|

Young Americans' ethnic identity toward disaster advertising: The effects of disaster location and message types

Abstract: The purpose of this study is to examine young American donors' perspectives toward disaster ad messages. Attitude toward helping others, social responsibility, ethnic identity on donation behavior, attitude toward ad, and advertising effectiveness were examined using 2 experimental variables (disaster location and message types). The findings explain that the constructs are positively related to each other and the 2 experimental variables significantly influence young Americans' attitudes toward ads and advert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…In general, cause marketing ads that feature an emotional appeal are more persuasive (Moriuchi and Chung, 2018). Additionally, storytelling increases donations (Merchant et al , 2010) and the best story that can be told to a prospective donor is to use a single, identifiable victim to arouse sympathy (Small, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, cause marketing ads that feature an emotional appeal are more persuasive (Moriuchi and Chung, 2018). Additionally, storytelling increases donations (Merchant et al , 2010) and the best story that can be told to a prospective donor is to use a single, identifiable victim to arouse sympathy (Small, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Examples include the Rails to Trails Conservancy, the Better Block Foundation, the National Complete Streets Coalition, the Central Park Conservancy and numerous other organisations that work with governments in public-private partnerships on infrastructure planning. In general, cause marketing ads that feature an emotional appeal are more persuasive (Moriuchi and Chung, 2018). Additionally, storytelling increases donations (Merchant et al, 2010) and the best story that can be told to a prospective donor is to use a single, identifiable victim to arouse sympathy (Small, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A neutral victim image condition was not included in the experimental design because a neutral emotion is rarely used in real-world prosocial campaigns. As well, extant literature suggests that emotional appeals are more effective than non-emotional messages in driving prosocial behaviors (Moriuchi & Chung, 2018). A total of 118 Americans (68 male; M age = 32.55, SD age = 8.97) between 18 and 71 years old were recruited via Amazon Mechanical Turk (MTurk).…”
Section: Methodsmentioning
confidence: 99%
“…With respect to direct financial donations alone, there is a large body of research looking at emotional appeals in charity advertising (Moriuchi & Chung, 2018; Goenka & van Osselaer, 2019; Septianto & Tjiptono, 2019). Notably, Moriuchi and Chung (2018) found that young Americans were more willing to donate when seeing emotional charity ads than when seeing factual messages. Other research has shown that the discrete positive emotion of pride could be beneficial in charitable advertising (Septianto & Tjiptono, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%